Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis